Tabletops for peace: Technology Enhanced Peacemaking in School Contexts - Ioannou, Andri; Antoniou, Chrystalla G. (My University, 2016)
This article describes an empirical investigation of technology-enhanced peacemaking in a conflict-stressed school environment. The peacemaking intervention required students in conflict-laden groups to collaborate on various game-like learning activities on a multitouch interactive tabletop, over the span of three weeks. Student interviews and video observations provided evidence that tabletops can become a means for communication and collaboration giving the chance for students in conflict to share a common space, shifting attitudes and improving their relationships. The study elaborates on the affordances of tabletops as they become apparent in the context of peacemaking, unpacking the still widely unexplored potential of multitouch interactive technology in peace education.
Keywords: Collocated collaboration; CSCL; CSCW; Interactive tables; Peace education; School conflict; Tabletops; Technology for peace; Technology for social change; Technology-enhanced learning; Technology-enhanced peacemaking